Incipient ameloblastoma or odontogenic hamartomatous proliferation: is BRAFV600E mutation helpful to distinguish them? - Souza, Lucas Lacerda de; Roza, Ana Luiza Oliveira Corrêa; Neri, André Luiz de Araújo; Soares, Ciro Dantas; Wright, John M.; Vargas, Pablo Agustin (Journal of Oral Diagnosis, 2024)
The distinction between odontogenic hamartomatous proliferation and other odontogenic cysts and tumors poses a diagnostic challenge. This report presents a unique case of an 18-year-old male who complained of pain and pus discharge in the right posterior mandible for three weeks. Upon intraoral examination, the patient presented with erythema and purulence in the posterior mandible, initially diagnosed as pericoronitis. Computed tomography revealed a well-defined, hypodense, and unilocular lesion attached to the cementoenamel junction of the right lower third molar. Histopathological examination of the surgically excised specimen indicated the presence of a cystic lesion lined by a reduced enamel epithelium, along with islands of hyperchromatic palisaded tumor cells with stellate reticulum-like arrangement scattered in a fibrous stroma in the deep portion of the oral mucosa. The initial diagnosis was an odontogenic hamartoma, but further analysis using immunohistochemistry for BRAF V600E and PCR to analyze the mutation in codon 600 of BRAF confirmed the diagnosis of incipient ameloblastoma. The patient has been under observation for 1 year and four months with no signs of recurrence.